UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN CENGKEH (Syzygium aromaticum L.) TERHADAP Streptococcus pyogenes - Ghaisani, Syifa Marha; Kurniati, Iis; Ilmi Sufa, Hafizah; Rahmat, Mamat (Jurnal Kesehatan Siliwangi, 2024)
One of the most common bacterial infections is pharyngitis. Most cases of acute pharyngitis are caused by viruses, but the main bacterial agent is Streptococcus pyogenes. Some antibiotics have been resistant to Streptococcus pyogenes, so alternative antibacterials are needed, namely the use of clove leaves (Syzygium aromaticum L.). The type of research used is Quasi Experiment. This study was conducted to test the antibacterial activity of clove leaves against Streptococcus pyogenes. Clove leaf extract was obtained by maceration method using 96% ethanol solvent. Phytochemical tests on clove leaf extracts showed positive leaves containing saponins, phenols, terpenoids, flavonoids, and tannins. Antibacterial activity test was conducted by disc diffusion method with variation of extract concentration of 10%, 15%, and 25% and incubation time for 24 and 48 hours. Bacitracin disc was used as positive control and negative control used 10% DMSO. The test results showed that there was antibacterial activity indicated by the formation of inhibition zone at 25% concentration with an average of 9.23 mm and 15% concentration of 8.8 mm. The zone of inhibition formed did not match the zone of inhibition in the control (≥13 mm).